Investigating Seronegative Phospholipase A2 Receptor Positive Primary Membranous Glomerulonephritis in a Young Adolescent Successfully Managed With Rituximab: Phospholipase A2 Receptor in Primary Membranous Glomerulonephritis - Kumar, Mritunjay; Prasad, Bimlesh; Patel , Kajal; Gupta, Sourabh (Journal of Pediatric Nephrology, 2024)
Membranous glomerulonephritis (MGN) is the most common cause of nephrotic syndrome in adults worldwide; however, it accounts for only 1.5% to 9% of cases of pediatric nephrotic syndrome. Detecting phospholipase A2 receptor (PLA2R) and thrombospondin domain containing 7A (THSD7A) among primary MGN patients has greatly transformed the diagnosis, treatment monitoring, and prognosis. These biomarkers are rarely undetected in the serum; however, renal tissue sent for histopathology is stained positive. Most of the previous reports of pediatric MGN are from adolescents approaching adulthood. We report a 9-year-old boy presenting with PLA2R-positive primary MGN who was seronegative and responded very well to 2 doses of rituximab after a failed steroid course.